The Epidemiology of Invasive Group B Streptococcus in Denmark From 2005 to 2018 - Hans-Christian Slotved; Steen Hoffmann (Frontiers Media S.A., 2020)
Previous epidemiology reports on invasive Streptococcus agalactiae (GBS) infections in Denmark did not include all patient age groups. The aim of this study was therefore to analyze the GBS incidence in all age groups during the period 2005-2018 and to present the serotype distribution and the antibiotic susceptibility. Data were retrieved from the Danish laboratory surveillance system, and these included data on typing and susceptibility testing for erythromycin and clindamycin. Early-onset disease (EOD) (mean incidence 0.17 per 1,000 live births) and late-onset disease (LOD) (mean incidence 0.14 per 1,000 live births) showed a low level during the period. The incidence was stable in the age groups 91 days to 4 years, 5-19 years, and 20-64 years. From 2005 to 2018, the incidence in the elderly showed a significantly increasing trend (P < 0.05), that in the 65-74 years increased from 3.23 to 8.34 per 100,000, and that in the 75+ years increased from 6.85 to 16.01 per 100,000. Erythromycin and clindamycin resistance fluctuated over the period; however, the overall trend was increasing. Data showed that EOD and LOD incidence continued to be low, whereas an increasing trend in GBS infections in the elderly was observed. The prevalence of erythromycin and clindamycin resistance increased from 2005 to 2018.